El uso de los emoticonos y la comunicación digital en WhatsApp por los estudiantes de la Escuela “Eduviges Portalet” - Rojas Cobos, Nathaly Katherine (2025)
Currently, digital communication has changed the way people communicate with each other, mainly in text applications such as WhatsApp, which contain elements such as emoticons or stickers that are used to express feelings and emotions, in addition to enhancing conversations. In this sense, this work aims to evaluate the use that emoticons have in WhatsApp digital communication by students of the school “Eduviges Portalet” in the city of Loja, Ecuador. For this, a mixed methodology was used, combining quantitative and qualitative approaches, also instruments such as survey, interviews, and a focus group were used. The results show that adolescents use the WhatsApp application daily to communicate among friends, emoticons or stickers are interpreted as important figures to express emotions quickly and easily. On the one hand, smilies are the emoticons most used by young people, highlighting their effectiveness in facilitating emotional communication. However, some of the students surveyed have differences about the words in certain contexts to avoid misunderstandings or mistakes. Finally, it is concluded by mentioning that emoticons not only help to improve digital communication on WhatsApp, but also, promote communication and emotional expression among young people, it should be noted that doing an exaggerated that of these figures can bring problems such as limiting the development of written language. This study also highlights the importance of understanding the impact of emoticons in youth communication, providing concrete bases for future research